2015
DOI: 10.1242/dev.105536
|View full text |Cite
|
Sign up to set email alerts
|

A pathway to bone: signaling molecules and transcription factors involved in chondrocyte development and maturation

Abstract: Decades of work have identified the signaling pathways that regulate the differentiation of chondrocytes during bone formation, from their initial induction from mesenchymal progenitor cells to their terminal maturation into hypertrophic chondrocytes. Here, we review how multiple signaling molecules, mechanical signals and morphological cell features are integrated to activate a set of key transcription factors that determine and regulate the genetic program that induces chondrogenesis and chondrocyte differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
461
3
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(482 citation statements)
references
References 206 publications
5
461
3
13
Order By: Relevance
“…Similarly, another previous study indicated that overexpression of Sma7 in mesenchymal progenitors (Prx1Cre) led to disturbed mesenchymal condensation associated with decreased Sox9 expression and poor cartilage formation by down-regulating the BMP-activated p38 pathway (Iwai et al 2008). TGF-b signals through Smad2/3 to interact with Sox9 and induces Sox9 transactivity; alternatively, TGF-b recruits the transcriptional coactivators CBP/p300 to increase Sox9 transactivity (Furumatsu et al 2005;Kozhemyakina et al 2015). Regardless of the little known facts about the post-translational regulation of Sox9, phosphorylation of Sox9 by protein kinase A (PKA) at Ser181 is associated with increase in transactivity (Huang et al 2001;Malki et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, another previous study indicated that overexpression of Sma7 in mesenchymal progenitors (Prx1Cre) led to disturbed mesenchymal condensation associated with decreased Sox9 expression and poor cartilage formation by down-regulating the BMP-activated p38 pathway (Iwai et al 2008). TGF-b signals through Smad2/3 to interact with Sox9 and induces Sox9 transactivity; alternatively, TGF-b recruits the transcriptional coactivators CBP/p300 to increase Sox9 transactivity (Furumatsu et al 2005;Kozhemyakina et al 2015). Regardless of the little known facts about the post-translational regulation of Sox9, phosphorylation of Sox9 by protein kinase A (PKA) at Ser181 is associated with increase in transactivity (Huang et al 2001;Malki et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Runx2 (Cbfa1) and Runx3 (Cbfa3) are required for chondrocyte maturation and indirectly function to enhance chondrocyte proliferation through promoting Ihh expression (Yoshida et al 2004). The balance between chondrocyte proliferation and hypertrophy is regulated by interactions between several signaling pathways, including IHH, PTH-related peptide (PTHLH), BMP, Wnt, and fibroblast growth factor (FGF) (Long and Ornitz 2013;Kozhemyakina et al 2015). The activity of Wnt and PTHLH signals regulates the level of calcium/ calmodulin-dependent protein kinase II (CAMK2), which induces chondrocyte hypertrophy in part through increasing RUNX2 and ÎČ-catenin activity Long and Ornitz 2013).…”
Section: Chondrogenesismentioning
confidence: 99%
“…8 Thus, in combination with the data from PTH1-34 treatments, our results demonstrate preservation in al ginate culture of the crucial functions that comprise the PTHrP IHH signaling feedback loop, a key node in the regulatory net work of growth plate cartilage. 2,5 Although treatment with IHH, PMA, or thyroxine resulted in similar effects on chondrocyte hypertrophy, we observed one crucial difference-both IHH and thryoxine treatments pro duced regional differences in chondrocyte hypertrophy in al ginate beads. Specifically, treatment with IHH or thyroxine was sufficient to stratify alginate bead cultures into an inner core consisting of nonhypertrophic (resting/proliferative) chondro cytes and an outer ring of ColXexpressing hypertrophic chon drocytes, which mimics the layered organization of growth plate cartilage in vivo.…”
Section: Ihh Signaling Establishes a Hypertrophic Zone In Alginate Cumentioning
confidence: 62%
“…1 Toward the distal (epiphyseal) end resides the resting (or reserve) zone that is composed of the least mature chondrocytes. 2 These resting zone chondrocytes are progres sively recruited into the proliferative zone, where cell cycle ac tivation and changes in cell morphology and cell organization result in expansion of isogenic columns of chondrocytes along the axis of growth. 3 As columns lengthen, chondrocytes at the proximal (meta physeal) end of the column withdraw from the cell cycle and increase in volume (hypertrophy) in two steps that are char acteristic of the prehypertrophic and the hypertrophic chon drocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation